New Standard Encyclopedia of Universal Knowledge: Volume XIV: Gershwin- Haggai - Frank H. Vizetelly 1864-1938 (New York Funk and Wagnalls Company, 1931)
prepared under the editorial direction of Frank H. Vizetelly, by an editorial staff of experts and specialists with the help of the leading scholars, scientists, and men of affairs of the English-speaking world
27 v. fronts. (ports.)illus.
Keywords: Encyclopedias (3GdehShYGJs; General; Encyclopedias and dictionaries